THE EFFORTS OF THE PROSPERITY IN ERADICING THE CRIME OF MONEY LAUNDERING (A Research in the Legal Area of the Medan District Attorney) - Akmal Samosir (PT Inovasi Pratama Internasional, 2022)
As for who became objective from study ie For know the role of the prosecutor's office in eradicating money laundering crimes, knowing the obstacles faced by prosecutors in eradicating money laundering crimes and knowing the efforts made by prosecutors in tackling money laundering crimes . Results study This show Role attorney in eradication follow criminal washing Money started from stage tracking , blocking , confiscation , confiscation And stage return . Obstacles encountered attorney in eradication follow criminal washing Money covers constraint juridical like overlap overlapping authority investigation And transaction finances done in a manner cash. Then constraint technical covering lack of understanding follow Criminal Washing Money By Regulated Society In Law No. 8 of 2010., Lack Courage investigator In Carry out the Investigation Process follow Criminal Washing Money , Lack Amount Owning Investigator Honesty High, Lack Quality / ability understanding investigator To follow Criminal Washing Money . Attempts made attorney in cope follow criminal washing Money through effort juridical And effort technical . Effort juridical like do coordination with operational Police And coordination With Affiliated institutions in the Criminal Justice System (CJS). This is Law enforcement officials should coordinate and cooperate well with all relevant agencies in implementing law enforcement against perpetrators of money laundering so that law enforcement efforts can run well and optimally. Coordination between law enforcement agencies needs to be improved so that there are no overlapping investigations nor money laundering investigation for the predicate crime, so that efforts to eradicate money laundering crimes can proceed quickly and in accordance with what is aspired to. It is advisable for law enforcement officers to carry out good socialization to all relevant agencies and the public in the implementation of law enforcement against perpetrators of money laundering crimes so that law enforcement efforts can run well and optimally.